Genetic diversity and structure of Atta robusta (Hymenoptera, Formicidae, Attini), an endangered species endemic to the restinga ecoregion - Reis,Evelyze Pinheiro dos (2014)
The genetic diversity and structure of the ant Atta robusta were assessed by ISSR (inter-simple sequence repeats) in 72 colonies collected from 10 localities in the Brazilian states of Espírito Santo (48 colonies) and Rio de Janeiro (24 colonies). The ISSR pattern included 67 bands, 51 of them (76.1%) polymorphic. Analysis of molecular variance (AMOVA) revealed a high level (57.4%) of inter-population variation, which suggested a high degree of genetic structure that was confirmed by UPGMA (unweighted pair-group method using an arithmetic average) cluster analysis. The significant correlation between genetic and geographic distances (r = 0.64, p < 0.05) indicated isolation that reflected the distance between locations. Overall, the populations were found to be genetically divergent. This finding indicates the need for management plans to preserve and reduce the risk of extinction of A. robusta.